MO481: Novel Predictors of CKD in Metabolic Fatty Liver Disease Patients: Steatosis Vs Fibrosis. A Prospective Study Using Transient Elastography With Controlled Attenuation Parameter. (3rd May 2022) - Marc, Luciana; Mihaescu, Adelina; Lupusoru, Raluca; Bob, Flaviu; Chisavu, Lazar; Timar, Bogdan; Timar, Romulus; Schiller, Adalbert
Abstract: BACKGROUND AND AIMS: Recent data have proven that NAFLD (nonalcoholic fatty liver disease) and NASH (nonalcoholic steatohepatitis) increase the risk of CKD. Changing the concept of NAFLD to MAFLD (metabolic dysfunction associated fatty liver disease) changes the data of inclusion of patients in the new category and also the relationship with CKD. Our study aimed to explore this relation using liver steatosis and liver fibrosis assessments by transient elastography (TE) with controlled attenuation parameter (CAP). METHOD: We prospectively evaluated 402 diabetic patients with MAFLD and high CKD risk using TE with CAP (FibroScan ® ). CKD was defined according to Kidney Disease Improving Global Outcomes (KDIGO) 2012 guidelines. Inclusion criteria: patients >18 years old and the presence of MALFD. Exclusion criteria: pregnancy, ascites, outliers, known chronic liver disease, decompensated liver disease, cardiac pacemaker, end-stage renal disease, heart failure, unreliable or invalid TE and CAP measurements, AST and ALT levels >5 times the upper limit of normal. Transient elastography was performed with the FibroScan ® device. To discriminate between fibrosis and steatosis stages, we used the TE and CAP cut-off values from a published multicentric trial compared with biopsy. Logistic regression and stepwise multiple logistic regression were used to evaluate the factors associated with CKD. In addition, ROC analysis was used to assess the performance of CAP and TE in predicting CKD. The study was conducted >1 year period. RESULTS: The prevalence of CKD in our group was 60.8%. Patients with CKD had higher mean LSM and CAP values than those without CKD (LSM 8.64 ± 4.30 versus 8.03 ± 6.57; P = .04 and CAP 320.09 ± 57.12 versus 306.29 ± 61.21; P = .04). We found that hepatic steatosis was a better predictor of CKD than fibrosis. Univariate regression showed that CAP values > 353 dB/m were predictive of CKD, and multivariate regression analysis (after adjustment according to sex, BMI, LDLc, HDLc and fasting glucose) showed that CAP values >353 dB/m were more strongly associated with the presence of CKD compared with LSM (fibrosis) values. CONCLUSION: In patients with MAFLD, CAP-assessed steatosis appears to be a better predictor of CKD compared with LSM-assessed hepatic fibrosis.